Metallothionein role in the kinetic model of copper accumulation and elimination in the clam Ruditapes decussatus - Serafim, A. (2020)
In order to clarify the role of metallothioneins (MT) in copper (Cu) toxicity, this work aimed to assess the involvement of this protein in the accumulation and elimination strategies of Cu in the clam Ruditapes decussatus exposed to two sublethal concentrations (25 and 50 microgCul(-1)). The behaviour of MT in three different tissues of clams during the accumulation and depuration processes was also followed by gel-filtration chromatography to assess if Cu was bound to MT or to other cytosolic components. The 96 h LC50 for water-borne copper was 715 microgL(-1) in R. decussatus. The Cu accumulation pattern was dependent on Cu exposure concentrations. In clams exposed to 25 microgl(-1), total Cu accumulation in the three tissues increased linearly during the exposure period, while in those exposed to 50 microgl(-1) it followed the first order kinetic model. The greatest amount of Cu accumulated in all tissues is associated to the low molecular weight cytosolic fraction (>50%). The chromatographic assay indicated that Cu in the cytosolic fraction is bound to MT and MT levels increase with the increase of Cu exposure confirming the binding affinity of Cu to MT in all tissues. However, a smaller percentage of Cu seems to be bond to other ligands, such as GSH. Copper was exponentially eliminated (only studied in clams exposed to 25 microgl(-1)) and the estimated half-life was tissue dependent (9, 5 and 14 days for the gills, digestive gland and remaining tissues, respectively). Copper bound to the thermostable compounds was eliminated more quickly (t(1/2)=4-7 days) in all tissues than those bound to the thermolabile compounds (t(1/2)=7-18 days). Interestingly, MT is rapidly degraded (t(1/2)=7 and 18 days), suggesting that this protein is actively involved in the elimination of this metal, through the Cu-MT complex since MT and Cu are turning over simultaneously. Therefore, when Cu exposure is low, the clam can cope efficiently with the excess of Cu levels by increasing MT induction as well as rapidly eliminating this metal via the MT-Cu complex. Copper toxicity in the clam R. decussatus is associated to the limited capacity of MT induction at higher and environmental unrealistic Cu exposures especially in the gills and remaining tissues.